Temperature Dependence of Exciton Diffusion in a Small‐Molecule Organic Semiconductor Processed With and Without Additive. (16th March 2015) - Lin, Jason D. A.; Mikhnenko, Oleksandr V.; van der Poll, Thomas S.; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> The temperature dependence of exciton diffusion in a small‐molecule organic semiconductor processed with and without additive is investigated. As‐cast and 1, 8‐diiodooctane‐processed films yield exciton diffusion lengths of 6.8 and 4.9 nm, respectively. Using a Monte Carlo simulation, it is shown that processing with 1, 8‐diiodooctane increases the excitonic trap density, which directly reduces the exciton diffusion length. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>